2001
DOI: 10.1029/2001wr000249
|View full text |Cite
|
Sign up to set email alerts
|

On the relative role of hydrodynamic dispersion for river water quality

Abstract: Abstract. Neglecting hydrodynamic dispersion in models of river water quality has important implications in terms of simplifying the equations which describe the system and for model calibration. In this paper we analyze the behavior of a river system subjected to a time-variable point source input of a degradable solute using frequency response techniques applied to one-dimensional solute transport models, considering the combined effect of amplitude attenuation and phase shift due to hydrodynamic dispersion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In general, the centroid of the distribution of trapped bottles should gradually shift downstream over time and the variance of the distribution should increase, approximately in accordance with advection-dispersion theory (e.g., Gandolfi et al, 2001). This is illustrated in Figure 5 which shows the predicted plastic bottle travel distance distribution 2, 5, and 10 days after injection, assuming arbitrarily that q(i) = 0.5 for all sub-reaches.…”
Section: Model Performance Beyond the Tracer Studysupporting
confidence: 75%
“…In general, the centroid of the distribution of trapped bottles should gradually shift downstream over time and the variance of the distribution should increase, approximately in accordance with advection-dispersion theory (e.g., Gandolfi et al, 2001). This is illustrated in Figure 5 which shows the predicted plastic bottle travel distance distribution 2, 5, and 10 days after injection, assuming arbitrarily that q(i) = 0.5 for all sub-reaches.…”
Section: Model Performance Beyond the Tracer Studysupporting
confidence: 75%
“…Computational results of the additional numerical tests with 0.01 D , not presented here, showed that the front shapes of the concentration profiles become more steep and the differences of the profiles of the IBCs become smaller as D decreases. The results agree qualitatively well with the theoretical analysis of Gandolfi et al (2001) who showed that the effect of the dispersion mechanism is negligible if R P is the order of 100 O or more. Nevertheless, the differences between the concentration profiles of the two IBCs are clearly not negligible under the presented conditions and are considered to become more significant for the problems with more complicated conditions.…”
Section: Computational Resultssupporting
confidence: 89%
“…5). For most elements, the maximum concentrations observed at Gibraleón were around 20-30% lower than those recorded at Sotiel, and the plume pass was more gradual owing to dispersion processes (Gandolfi et al, 2001). However, the maximum Fe concentration was almost 60% lower than at Sotiel (Fig.…”
Section: Impacts On the Odiel Rivermentioning
confidence: 84%